ENFORCEMENT OF DECISIONS ON CHILD RESIDENCE AND CONTACT ORDERS CONCERNING THE CHILD IN LIGHT OF NOVELTIES IN CROATIAN LAW AND EUROPEAN LAW - Aras Kramar, Slađana (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2020)
The paper contains an analysis and discussion of the novelties introduced by the Croatian Family Act of 2015 in the enforcement proceedings for handing over the child to the person entitled to custody and exercising access rights with the child, taking into account the procedural subjectivity and position of the child (especially her/his right to express opinions and thus influence the course of enforcement proceedings) as well as the significance of the methods of professional work of the social welfare center and family mediation on this procedure. Then, the author discusses and evaluates the new solutions of the Brussels II ter Regulation in the field of recognition and enforcement of decisions in cases of parental responsibility with a cross-border element in the light of procedural rights of the child and the need to achieve effective enforcement, as well as of the circumstances of grave risk to the child that may affect the enforcement of decisions in parental responsibility cases issued in another EU Member State. In the concluding part of the paper, the author presents a summary synthesis of the main results of the research, as well as certain de lege ferenda recommendations.
Keywords: enforcement; handing a child over to the person entitled to custody; exercise of access rights; child; parent; procedure; Croatian law; BR II bis; BR II ter